Phase I Study of Anti-CD3 x Anti-Her2 Bispecific Antibody in Metastatic Castrate Resistant Prostate Cancer Patients - Ulka Vaishampayan; Archana Thakur; Ritesh Rathore; Nicola Kouttab; Lawrence G. Lum (Prostate Cancer)
Background. New nontoxic targeted approaches are needed for patients with castrate resistant prostate cancer (CRPC). Our preclinical studies show that activated T cells (ATC) armed with anti-CD3 x anti-Her2 bispecific antibody (Her2Bi) kill prostate cancer cells lines, induce a Th1 cytokine pattern upon engagement of tumor cells, prevent the development of prostate tumors, and retard tumor growth in immunodeficient mice. These studies provided strong rationale for our phase I dose-escalation pilot study to test ATC armed with Her2Bi (aATC) for safety in men with CRPC. Methods. Seven of 8 men with CRPC were evaluable after receiving two infusions per week for 4 weeks. The men received 2.5, 5 or 10 × 109 aATC per infusion with low dose interleukin-2 and granulocyte-macrophage colony stimulating factor. Results. There were no dose limiting toxicities, and there was 1 partial responder and 3 of 7 patients had significant decreases in their PSA levels and pain scores. Immune evaluations of peripheral blood mononuclear cells in 2 patients before and after immunotherapy showed increases in IFN-γ EliSpot responses and Th1 serum cytokines. Conclusions. These results provide a strong rationale for developing phase II trials to determine whether aATC are effective for treating CRPC.